2022
DOI: 10.3390/cancers14184501
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment CD14+ Cells Correlate with Poor Overall Survival in Patients with Early-Stage Lung Adenocarcinoma

Abstract: Patients with early-stage lung adenocarcinoma have a high risk of recurrent or metastatic disease despite undergoing curative intent therapy. We hypothesized that increased CD14+ cells within the tumor microenvironment (TME) could stratify patient outcomes. Immunohistochemistry for CD14 was performed on 189 specimens from patients with lung adenocarcinoma who underwent curative intent surgery. Outcomes and associations with clinical and pathologic variables were determined. In vitro studies utilized a cocultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…APOA4 was found over expressed in the serum and the respiratory epithelium of atypical adenomatous hyperplasia patients [15]. CD14 + cells play an important role in tumor microenvironment, and a recent study shows that levels of CD14 + cells negatively correlate with overall survival of lung cancer patients [16], and CD14 + macrophages may exert a broader function in other cancers as well. As an actin-binding protein, profilin (PFN1) has been reported to induce tumor metastasis in non-small cell lung cancer [17].…”
Section: Discussionmentioning
confidence: 98%
“…APOA4 was found over expressed in the serum and the respiratory epithelium of atypical adenomatous hyperplasia patients [15]. CD14 + cells play an important role in tumor microenvironment, and a recent study shows that levels of CD14 + cells negatively correlate with overall survival of lung cancer patients [16], and CD14 + macrophages may exert a broader function in other cancers as well. As an actin-binding protein, profilin (PFN1) has been reported to induce tumor metastasis in non-small cell lung cancer [17].…”
Section: Discussionmentioning
confidence: 98%
“…67 Schenk et al also showed early-stage adenocarcinoma patients with increased CD14 + cells experienced a lower median OS of 5.5 years compared to 10.7 years for those with moderate or low CD14 expression levels. 68 This negative effect is most likely caused by the role of myeloid-derived suppressor cells (MDSCs), in encouraging tumor spread and contributing to an immunosuppressive environment. 69,70 We also confirmed that increased stromal CD14 is strongly related to poor survival outcomes corroborating the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…One study revealed that the preoperative neutrophil‐lymphocyte ratio is an independent prognostic factor in patients with LUAD after complete resection and could be considered a prognostic marker for LUAD after complete resection 14 . CD14 + cells have been identified as a biomarker of poor prognosis in the early stage of LUAD and could promote the survival of LUAD patients 15 . Another study found that a higher numbers of CD8 + cells in tumor tissues is associated with better overall survival than a moderate or low number of CD8 + cells and is considered a protective factor in LUAD patients 16 .…”
Section: Introductionmentioning
confidence: 99%
“… 14 CD14 + cells have been identified as a biomarker of poor prognosis in the early stage of LUAD and could promote the survival of LUAD patients. 15 Another study found that a higher numbers of CD8 + cells in tumor tissues is associated with better overall survival than a moderate or low number of CD8 + cells and is considered a protective factor in LUAD patients. 16 Therefore, immune cells in LUAD have tremendous research value for investigating the prognosis of LUAD and formulating new therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%